Pengaruh Pengalaman Magang, Hasil Belajar Produktif dan Dukungan Sosial Keluarga terhadap Kesiapan Kerja Mahasiswa - Reni Diah Setiowati; Robi Santoso (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
Readiness for the world of work for students is something that needs to be considered together, because it is related to the student's future. Generally, each study program has its own program to create graduates who are ready to enter the world of industry. This research aims to determine: (1) the level of students' readiness to enter the industrial world, (2) students' competitive ability in entering the industrial world, (3) the relationship and influence of internship experience, productive learning outcomes and family social support on students' readiness to enter industrial world. This research is an ex-post facto type research with a correlation research design. The results of the descriptive analysis show that the level of student work readiness in entering the industrial world is 36.65% of students have a very high level of work readiness, and 63.35% of students have a high level of work readiness. The results of hypothesis testing show that there is a positive and significant influence between student internship experience, productive learning outcomes and family social support on students' work readiness to enter the industrial world, with the contribution given being 32.7% (R2 = 0.327). This explains that student internship experience, productive learning outcomes and family social support together are able to explain the variance in student work readiness by 32.7%.